Gas-diffusion microextraction - Joao Grosso Pacheco (2010)
Gas diffusion microextraction (GDME) is an innovative technique that combines the advantages of membrane aided gas diffusion with microextraction concepts GDME makes uses of a novel portable and low cost device that comprises a small commercially available semi permeable membrane Furthermore if derivatization is integrated into the GDME concept considerable enrichment factors can be obtained It may become a powerful tool for any analyst who intends to quantify volatile and semi volatile analytes in various kinds of matrices The analysis of vicinal diketones in beer was used as a case study to show GDME applicability and capabilities Vicinal diketones were derivatized with o phenylenediamine and then determined by HPLC UV Obtained results showed good repeatability and precision with extraction periods at the minute time span